Eagle's syndrome: A rare case of young female - Mohammad Abdul Baseer; Mohammed Suliman Alenazy (Wolters Kluwer Medknow Publications, 2013)
Eagle's syndrome is a condition that causes pain in the Craniofacial and cervical region of the neck. Symptoms related to the Eagle's syndrome may be confused with the variety of neuralgias, oral, dental and temporomandibular joint (TMJ) conditions. In this paper, a case of the very young female suffering with the difficulty in swallowing and recurrent dull pain in the throat with restriction of the movement of head to the left side was presented. A thorough past medical and dental history, extra oral and intra oral examination coupled with the panoramic radiographic interpretation were used to diagnose Eagle's syndrome.